2004
DOI: 10.1023/b:pham.0000026443.71935.cb
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Blends Used for the Coating of Multiparticulates: Comparison of Aqueous and Organic Coating Techniques

Abstract: The type of coating technique strongly affects the film microstructure and, thus, the release mechanism and rate from pellets coated with polymer blends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 5 publications
2
55
0
Order By: Relevance
“…Thus, RL and L55 copolymer chains are highly entangled, and therefore, leaching out of L55 into the surrounding medium is minimized. Such behavior has been described before for film blends of ethyl cellulose and L55 prepared from organic solution (31). Additionally, the ionic interactions between the copolymers might also contribute to the prevention of leaching out of L55 during exposure to phosphate buffer pH 6.8.…”
Section: Investigation Of the Erosion Of Plain Copolymer Films And Fisupporting
confidence: 69%
“…Thus, RL and L55 copolymer chains are highly entangled, and therefore, leaching out of L55 into the surrounding medium is minimized. Such behavior has been described before for film blends of ethyl cellulose and L55 prepared from organic solution (31). Additionally, the ionic interactions between the copolymers might also contribute to the prevention of leaching out of L55 during exposure to phosphate buffer pH 6.8.…”
Section: Investigation Of the Erosion Of Plain Copolymer Films And Fisupporting
confidence: 69%
“…Apart from being used for the preparation of the core of monolithic matrices, polymer blending was also studied in the aim to modify the permeability characteristics of the film in solid dosage forms coated with cellulose esters (73)(74)(75)(76)(77)(78)(79). These studies demonstrated that the drug release kinetics can be modulated by altering the coating characteristics, and consequently the drug release mechanism, via the introduction of a "non-coating agent" in the film composition.…”
Section: The Need Of Innovative Materials For Intelligent Delivery Inmentioning
confidence: 99%
“…[9] Further, blending of polymers has also been used to create films with tailored interfacial properties for controlling drug release from microparticles. [10,11] The unique benefit that blending affords has recently been applied to PEs in tandem with the LbL approach to tailor the physicochemical properties of surfaces, thus producing highly functional films and coatings with nanoscale dimensions and tailored interfacial properties assembled from aqueous solutions. Two distinct types of PE blends have been identified in the current literature.…”
Section: Introductionmentioning
confidence: 99%